2020
DOI: 10.1177/0976399620948318
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure Equity and Firm Performance in India

Abstract: The growing financing requirements coupled with tightening of fiscal purse strings point to the pertinence of market-based finance for infrastructure provision and enhancement. For this, the question of the sectoral performance of infrastructure takes centre stage and this becomes the basis for the present study. The study assesses the risk-return and volatility profile of Nifty Infra, the National Stock Exchange (NSE) sectoral index for the 30 biggest infrastructure firms in India vis-à-vis the broader Nifty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Marzuki and Newell (2021a) and Marzuki and Newell (2021b) used a unique data set of both listed and unlisted infrastructure to examine its portfolio diversification potential to find significant results in favor of infrastructure. Apart from this, two recent studies based on Indian data, Hasnat (2021) and Majumder (2021), found no significant evidence of stable cash flows by infrastructure investments. Similarly, Bianchi et al (2014) explored the separate asset class status of listed infrastructure in the USA and concluded against it.…”
Section: Introductionmentioning
confidence: 77%
“…Marzuki and Newell (2021a) and Marzuki and Newell (2021b) used a unique data set of both listed and unlisted infrastructure to examine its portfolio diversification potential to find significant results in favor of infrastructure. Apart from this, two recent studies based on Indian data, Hasnat (2021) and Majumder (2021), found no significant evidence of stable cash flows by infrastructure investments. Similarly, Bianchi et al (2014) explored the separate asset class status of listed infrastructure in the USA and concluded against it.…”
Section: Introductionmentioning
confidence: 77%
“…Numerous recent studies focus on the risk-return profiles of infrastructure and their overall benefits in the investment context (Marzuki et al, 2020). Their performance has been explored not only in the United States (Newell & Peng, 2008), but also in multiple countries, such as Australia (Newell et al, 2011), China (Newell et al, 2009), India (Hasnat, 2021;Majumder, 2021;Singhal et al, 2011), the United Kingdom (Oyedele et al, 2013), or Jordan (Gharaibeh, 2019). Most studies indicate that they offer higher profits and less risk than most liquid asset classes, such as stocks or bonds, but may be outperformed by, for example, private equity (Inderst, 2009).…”
Section: Related Literaturementioning
confidence: 99%
“…Two recent studies examine the performance of infrastructure using listed Indian data. While Hasnat ( 2021 ) uses a composite Nifty infra index, Majumder ( 2021 ) uses eight different Nifty thematic indices including energy and infrastructure. Based on standard CAPM and M-GARCH, Hasnat ( 2021 ) finds lower returns and lower volatility for Nifty infra as compared to Nifty 50.…”
Section: Reporting the Findingsmentioning
confidence: 99%
“…While Hasnat ( 2021 ) uses a composite Nifty infra index, Majumder ( 2021 ) uses eight different Nifty thematic indices including energy and infrastructure. Based on standard CAPM and M-GARCH, Hasnat ( 2021 ) finds lower returns and lower volatility for Nifty infra as compared to Nifty 50. Also, the author concludes that the asset class is more prone to exchange rate changes indicating large foreign investment.…”
Section: Reporting the Findingsmentioning
confidence: 99%